2005
DOI: 10.1007/s00520-005-0843-2
|View full text |Cite
|
Sign up to set email alerts
|

No pain relief from morphine?

Abstract: This study has shown that proactive clinical identification and management of patients that require opioid switching is reproducible in different clinical settings and significantly improves pain control. Further studies are required to develop and test the predictive model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…It can be used safely in elderly patients and in mild/moderate renal impairment [42,43,44,45]. Patient preference for oxycodone compared to morphine has also been identified [46, 47]. …”
Section: Why Use Oxycodone?mentioning
confidence: 99%
“…It can be used safely in elderly patients and in mild/moderate renal impairment [42,43,44,45]. Patient preference for oxycodone compared to morphine has also been identified [46, 47]. …”
Section: Why Use Oxycodone?mentioning
confidence: 99%
“…Five open-label studies on oxycodone and cancer pain were also identified (table 2) [18,19,20,21,22]. The total number of patients followed by these studies was 608.…”
Section: Resultsmentioning
confidence: 99%
“…There was a sustained efficacy over long periods of time and most side effects were tolerable. One of the studies uses oxycodone as a first-line alternative opioid to morphine for opioid rotation or switching [22]. …”
Section: Resultsmentioning
confidence: 99%
“…However, none could be identified by Maier et al [44]. In 2006, Riley et al [7] introduced a clinically objective model for predicting switchers (patients not responding to morphine who should be switched to other opioids or other analgesic treatments). They stated that the model was in its infancy and had no use in clinical practice in the presented form and needed further development by the addition of genetic and immunological data.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been used to identify common alterations in the EPs for a group of subjects after drug administration in comparison to pretreatment or placebo recordings [6]. However, the study of group alterations is a crude approximation when describing the mechanisms of action for analgesics, since it is well known that individuals display a large variation in efficacy to analgesics such as opioids [7]. Hence, new methods to quantify individual alterations in the EPs are warranted.…”
Section: Introductionmentioning
confidence: 99%